Evidence of Aalenian-stage palaeofires in an extremely thick coal seam of the eastern Junggar Basin, Xinjiang, China - Zhang, Qin; Feng, Shuo; Yang, Bo; Li, Xin; Wang, Wenfeng; Tian, Jijun; Wang, Xingli (Frontiers in Earth Science, 2025)
Scholars increasingly support the hypothesis that inertinite in coal is the product of incomplete combustion of plants in coal-forming peat swamps during fire events. In this study, charcoal fragments were extracted from an extremely thick coal seam in the Wucaiwan mining area in the eastern Junggar Basin. The temperatures that caused palaeofires were then estimated using a reflective light microscope. The inertinite reflectance data (average 1.26%) indicated the formation of these charcoal fossils at temperatures of 300°C–400°C. Additionally, the content characteristics of 16 polycyclic aromatic hydrocarbons (PAHs) in the coal rock samples were determined by rapid solvent extraction by analyzing inertinite and reflectance data of samples from the Xishanyao Formation in the eastern Junggar Basin. The palaeofire events experienced by the coal seams during deposition were comprehensively analyzed. The PAH test results showed significant variation in PAH content between layers, ranging from 3,881 to 6,525 ng/g, with an average of 4,433 ng/g. Moreover, different PAHs within the same layer exhibited considerable variations in content. The integration of inertinite content, inertinite reflectance, and PAH characteristics led to the conclusion that the coal seam experienced at least three periods of frequent palaeofires during deposition. Combining these findings with charcoal reflectance data suggested that the palaeofires during these periods were predominantly low-to medium-temperature ground fires.